ORGANIC FOOD POSITIONING: HOW DO COMPANIES WANT THEIR BRAND TO BE PERCEIVED BY CONSUMERS? - Mihai STOICA (Management & Marketing)
The intensification of consumers' concerns for personal health protection has conducted, among other things, to a change in purchasing behavior toward organic food. However, emerging markets are still characterized by low levels of organic food consumption. Therefore, companies present on this market are trying to find new ways to boost the consumption of organic food, along with placing their brands in the most favorable positions in the minds of consumers. This study aims to identify the positioning bases that companies want to highlight in order to outline the desired position of their brand. To achieve this goal, a qualitative research was conducted among producers/processors, distributors/importers, and retailers having organic food brands in their portfolio. The results of the research showed the focus of the companies on highlighting the attributes related to the product characteristics and the personal green benefits, at the expense of environmental, emotional, and symbolic benefits. Positioning bases related to consumption occasions, brand values, and association with fictional characters or celebrities play a secondary role in supporting the brand position. The research contributes to the classification and conceptualization of specific positioning bases for organic food brands, providing an overview of this topic at the supply chain level.